An Analysis of Inflectional and Derivational Affixes of the Students’ Academic Writing - Stanislaus Guna; Irene Nindiana Lehon; Maksimilianus Sapong; Angelus Rico Sambora; Yohanes Tresno Kurnianto (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study investigates the use of inflectional and derivational affixes in the academic writing of second–year English students, identifying the challenges they face in applying these linguistic elements. Using qualitative methods, specifically content analysis, this study examined a sample of 30 students' writings from the 2021C class. The analysis identified a total of 172 affixes: 122 inflectional suffixes, 36 derivational suffixes, and 14 derivational prefixes. Inflectional suffixes, particularly irregular forms, were predominantly used, while derivational affixes primarily served to change grammatical classes, with